The causes of path inflation. - Spring, Neil (Computer communication review.)
Researchers have shown that the Internet exhibits path inflation -- end-to-end paths can be significantly longer than necessary. We present a trace-driven study of 65 ISPs that characterizes the root causes of path inflation, namely topology and routing policy choices within an ISP, between pairs of ISPs, and across the global Internet. To do so, we develop and validate novel techniques to infer intra-domain and peering policies from end-to-end measurements. We provide the first measured characterization of ISP peering policies. In addition to "early-exit," we observe a significant degree of helpful non-early-exit, load-balancing, and other policies in use between peers. We find that traffic engineering (the explicit addition of policy constraints on top of topology constraints) is widespread in both intra- and inter-domain routing. However, intra-domain traffic engineering has minimal impact on path inflation, while peering policies and inter-domain routing lead to significant inflation. We argue that the underlying cause of inter-domain path inflation is the lack of BGP policy controls to provide convenient engineering of good paths across ISPs.